2009
DOI: 10.1021/ci800447g
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Protein−Ligand Fingerprint To Mine Chemogenomic Space: Application to G Protein-Coupled Receptors and Their Ligands

Abstract: The present study introduces a novel low-dimensionality fingerprint encoding both ligand and target properties which is suitable to mine protein-ligand chemogenomic space. Whereas ligand properties have been represented by standard descriptors, protein cavities are encoded by a fixed length bit string describing pharmacophoric properties of a definite number of binding site residues. In order to simplify the cavity fingerprint, the concept was applied here to a unique family of targets (G protein-coupled recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 80 publications
(136 reference statements)
2
113
1
Order By: Relevance
“…In the teeth of current opinion, we found that few drugs lack reasonable primary targets, at least among domain experts. The ability of chemoinformatics methods to rapidly identify targets, and to predict those which can be experimentally confirmed, supports the idea that this and related methods (11,12,(46)(47)(48) will be useful in target identification for drugs that emerge from nontarget-based methods. Even in this molecular era of drug discovery, there remain new investigational drugs whose molecular targets are unclear, restricting their optimization and broad use in disease.…”
Section: Discussionmentioning
confidence: 65%
“…In the teeth of current opinion, we found that few drugs lack reasonable primary targets, at least among domain experts. The ability of chemoinformatics methods to rapidly identify targets, and to predict those which can be experimentally confirmed, supports the idea that this and related methods (11,12,(46)(47)(48) will be useful in target identification for drugs that emerge from nontarget-based methods. Even in this molecular era of drug discovery, there remain new investigational drugs whose molecular targets are unclear, restricting their optimization and broad use in disease.…”
Section: Discussionmentioning
confidence: 65%
“…Examples include the similarity ensemble approach developed by Keiser et al [346], three-dimensional shape based approach for identifying diverse targets [358], structural similarities of molecular scaffolds to map drug promiscuity GPCRs by encoding both, ligand descriptors and protein pharmacophoric properties, in a low dimensional fingerprint for chemogenomic screening applications [172]. Text mining approaches [361] and semantic framework based methods [362] have been applied to map and predict polypharmacology using widely available biochemical information contained in publicly available resources.…”
Section: Polypharmacology: Selectivity or Promiscuity? Or Both?mentioning
confidence: 99%
“…1b) [172]. Their method combines standard fingerprint representations of ligand with a protein "cavity fingerprint (CavFP)" representing pharmacophore features of protein binding site residues.…”
Section: Structure-based Pharmacophore Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel yet critical requirement is on explicit target-ligand complex/relationship representation (i.e., representing the binding event/relationship between biologicals and chemicals). In chemogenomics-based methods, the complexes are represented/modeled by protein-ligand fingerprints [Weill and Rognan, 2009], protein and ligand descriptor concatenation [Bock and Gough, 2005], protein space and ligand space tensor product and kernel fusion [Jacob and Vert, 2008], among others.…”
Section: Data Representation For Chemogenomics-based Sarmentioning
confidence: 99%